Acinetobacter baumannii clonal lineages I and II harboring different carbapenem-hydrolyzing-β-lactamase genes are widespread among hospitalized burn patients in Tehran. Issue 6 (November 2015) - Mahdian, Somayeh; Sadeghifard, Nourkhoda; Pakzad, Iraj; Ghanbari, Fatemeh; Soroush, Setareh; Azimi, Lila; Rastegar-Lari, Abdolaziz; Giannouli, Maria; Taherikalani, Morovat
Summary The aim of this study was to analyze antimicrobial resistance patterns and their encoding genes and genotypic diversity of Acinetobacter baumannii isolated from burn patients in Tehran, Iran. The presence of extended-spectrum beta-lactamase- and blaOXA-encoding genes among 37 multidrug resistant (MDR) A. baumannii strains isolated from patients hospitalized in a teaching hospital in Tehran was evaluated. Susceptibility to 7 antibiotics was tested by disk agar diffusion and to polymyxin B and colistin was tested by E-test, according to CLSI guidelines. All isolates were then analyzed by PCR for the presence of blaIMP, blaVIM, blaSIMblaOXA-23, blaOXA-24, and blaOXA-58-like carbapenemase genes, and blaOXA-51-like, blaTEM, blaSHV, blaPER, blaVEB, and blaGIM genes. Genotyping of A. baumannii strains was performed by repetitive sequence-based (REP)-PCR and cluster analysis of REP-PCR profiles. A. baumannii isolates were assigned to international clones by multiplex PCR sequence group analysis. Twenty-five A. baumannii isolates were classified as MDR, and 12 were classified as extensively drug resistant. All isolates were susceptible to colistin and polymyxin B. Eighty-one percent of the isolates was resistant to imipenem or meropenem and harbored at least one or both of the blaOXA-23-like or blaOXA-24-like carbapenemase genes. Co-existence of different resistance genes was found among carbapenem-resistant isolates. Multiplex PCR sequence group analysis most commonly assigned A. baumannii isolates to international clones I (18/37; 48.6%) and II (18/37; 48.6%). An alarming increase in resistance to carbapenems and the spread of blaOXA-23-like and/or blaOXA-24-like carbapenemase genes was observed among A. baumannii strains belonging to clonal lineages I and II, isolated from burn patients in Tehran.